Classificação espectral e determinação de distância de estrelas em dez regiões HII do hemisfério sul - Pinheiro, Márcio do Carmo (2009)
In order to determine distances of Southern Galactic HII regions, we carried out spectroscopic and photometric observations of the stellar content of a set of these objects. We have chosen objects only visible in the South hemisphere, with no published or uncertain distances. In this work, we present spectral classification based on intermediate dispersion spectra with a very high signal to noise ratio and on stellar UBV photometry, so that the distances have been determined using the usual method, the spectroscopic parallax. We picked up the 2MASS infrared photometry and assessed the reddening individually for each star, using the color-difference method. This way, we have estimated the totalto-selective extinction ratio for the most of the classified stars, and so, we have found a mean value 21% higher than the mean value of RV calculated on the whole directions of the Galaxy. As a result, we have found distances in general smaller than those already published on the literature, although confirming several spectral classifications. Besides that, large fluctuations around the values normally adopted were also observed, which would result in larger discrepancies between the stellar distances. At last, we have also extracted nebulae spectra in order to estimate the kinematics distances, so that we could compare the distance measurement results by different methods. In general, we have found reasonably compatible distances. However, in some cases large differences was found, suggesting that some objects present deviations of the circular motion.